Circular RNAs as diagnostic biomarkers for gastric cancer: A comprehensive update from emerging functions to clinical significances - Xu, Chun-Yi; Zeng, Xi-Xi; Xu, Li-Feng; Liu, Ming; Zhang, Feng (Frontiers in Genetics, 2022)
The incidence and mortality of gastric cancer is still high worldwide, especially in East Asia. Due to the lack of specific manifestations in early stage, most patients have progressed into the advanced stage when diagnosed in most developing countries. Therefore, it is urgent to find more sensitive and reliable biomarkers to enable early screening of gastric cancer. Circular RNA (circRNA) is a highly conserved and stable closed circular non-coding RNA. In recent years, a lot of literature has shown that the abnormal expression of circRNAs is related to the occurrence of gastric cancer, and suggests that circRNA may serve as a potential biomarker for gastric cancer diagnosis. In this paper, we reviewed the structural characteristics, formation mechanism and biological function of circRNA, as well as research progress and existing problems in early screening of gastric cancer.